LIPID PEROXIDATION AND ANTIOXIDANT PROTECTION IN PERIODONTAL TISSUES UNDER THE ACTION OF LOCAL PATHOGENIC FACTOR ON GUMS IN RATS EXPOSED TO MODELED SYSTEMIC INFLAMMATORY RESPONSE - A.M. Yelins’ka; V.O. Kostenko (Проблеми екології та медицини)
The purpose of the work was to study the state of lipid peroxidation (LPO) and antioxidant system in periodontal tissues under the influence of the local pathogenic factor on the gums in rats against modeled systemic inflammatory response (SIR) reproduction. The study was carried out on 40 white male rats of the Wistar line weighing 180-220 g, divided into 4 groups: the 1st included intact animals, the 2nd was made up by animals subjected to SIR modeling, the 3rd included animals, which were subjected to modeled acute gingivitis by applying 5% sodium hydroxide (NaOH) solution onto their gums, and the 4th group involved rats with acute gingivitis induced by 5% NaOH solution against modeled SIR. SIR was induced by intraperitoneal administration of lipopolysaccharide Salmonella typhi (pyrogenalum) in a dose that stimulated rise in temperature by 1.5 °C. During the following seven weeks of the experiment, rats were given 4 MPD / kg of body weight once a week. To simulate the action of local pathogenic factor affecting the gums we used the modeled acute gingivitis. For this purpose we irrigated the rats’ gums with 5% NaOH solution through 10 s. The simulation of SIR is accompanied by the development of decompensated LPO in periodontal tissues, by the decrease in their antioxidant potential as well as the activity of superoxide dismutase and catalase. The application of 5% NaOH solution onto the gums is accompanied by the development of compensated LPO in periodontal tissues with an increase in the activity of superoxide dismutase and catalase. The application of 5% NaOH solution onto the gums against modeled SIR causes an increase in the production of by-products of LPO in periodontal tissues and reduced their antioxidant potential, as well as the activity of superoxide dismutase and catalase compared to separate simulations of SIR and acute gingivitis.